2018
DOI: 10.1177/1471301218816814
|View full text |Cite
|
Sign up to set email alerts
|

Economic costs and health-related quality of life associated with individual specific reminiscence: Results from the InspireD Feasibility Study

Abstract: Recent studies have focused on the use of technology to support reminiscence but there remains a dearth of research on the health costs and benefits associated with this intervention. The aim of this study was to estimate costs and quality of life associated with a home based, individual specific reminiscence intervention, facilitated by an iPad app for people living with dementia and their family carers, with a view to informing a future cost-effectiveness analysis. Use of community health and social care ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Results showed that there was an overall increase in health‐related quality of life over the duration of the intervention. Recipients of e‐health had a significantly lower rate of emergency room visits (rate difference 9.5%, p = 0.048) and hospital stays (rate difference 11.4%, p = 0.01) over the 6‐month course of the intervention than usual care 42 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that there was an overall increase in health‐related quality of life over the duration of the intervention. Recipients of e‐health had a significantly lower rate of emergency room visits (rate difference 9.5%, p = 0.048) and hospital stays (rate difference 11.4%, p = 0.01) over the 6‐month course of the intervention than usual care 42 …”
Section: Resultsmentioning
confidence: 99%
“…Six studies conducted cost‐consequence analysis 34,36,37,39,42,44 . A variety of health or non‐health‐related outcome indicators were selected for inclusion and were not limited to QALY.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eleven interventions identi ed using tablet-computer driven technologies, the most reviewed system was CIRCA, developed as a prototype to support and promote communication between PwD and their caregivers [13][14][15]. The software program is based on reminiscence, a therapy form that is widely recognized to contribute to actively engaging PwD and improve their wellbeing [16][17][18]. CIRCA is referred to as a "cognitive prosthesis" by its creators, as the system uses reminiscence as a basis for the conversation [3,13].…”
Section: Tablet Computersmentioning
confidence: 99%
“…The articles by McAllister et al (2017), Ferry et al (2018), and Ryan et al (2018) reported the results of digital apps that support reminiscences and meaningful engagement with carers. Finally, the article by Gibson et al (2016) is a scoping review that explored the provision of assistive technology products available for people with dementia.…”
mentioning
confidence: 99%